1977
DOI: 10.1038/hdy.1977.21
|View full text |Cite
|
Sign up to set email alerts
|

Selection for mating success of yellow mutant Drosophila melanogaster: biometrical genetic analysis

Abstract: A biometrical genetic analysis was conducted on two lines of Drosophila melanogaster that had been selected for wild-type female receptivity and for high mating success of yellow mutant males. Simple additive-dominance models were adequate only for male mating ability measured over 1-hour mating periods. The genetic models for female receptivity required the inclusion of sex-linkage, maternal genetic effects and digenic interactions. Some of the genetic parameters were found to change with the duration of test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…The results with M2 males are different, since in this diallel dominance is basically for high receptivity, in clear contrast with the dominance for low receptivity observed by Dow (1977).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The results with M2 males are different, since in this diallel dominance is basically for high receptivity, in clear contrast with the dominance for low receptivity observed by Dow (1977).…”
Section: Discussioncontrasting
confidence: 77%
“…When these selected lines were subjected to a Cavalli biometrical analysis (Dow, 1977), the genetic model for receptivitiy in an observation period of 1 h contained additive, dominance and maternal components in one selected line, and additive and dominant sex-linked components in the other line. In both lines, dominance was for low receptivity.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown here that the answer lies in the mating propensity of the flies used. It is well recognized that mating propensity varies among populations of Drosophila, and there is also a large intrapopulational variation for this trait (Manning 1961;Kessler 1969;Manning and Hirsch 1971;Dow 1977;Singh and Chatterjee 1988;Carracedo et al 1991;Casares et al 1992Casares et al , 1993.…”
Section: Discussionmentioning
confidence: 99%
“…At least 70 vials were observed for each population. The raw data, in seconds, were log-transformed to obtain a normal distribution (Dow 1976). Because not all flies mated during the observation period, we followed a procedure outlined by Manning (1961) that permits the extrapolation of mean and variance of truncated data (the observed matings only).…”
Section: Mating Propensitymentioning
confidence: 99%
“…Their results revealed a genetic architecture of additive genetic variation and directional dominance for fast mating speed. Dow (1977) performed a Cavalli cross for two lines of D. melanogaster that had been selected for wild-type female receptivity and for high mating success of yellow (y) mutant males. The results showed that for male mating success a simple additive-dominance model adequately described the data, dominance being for higher mating success.…”
Section: Introductionmentioning
confidence: 99%